Extrato oleoso de urucum na alimentação de frangos de corte - Luiggi, Fabiana Golin [UNESP] (2015)
The objective of this experiment was to evaluate the inclusion of increasing levels of annatto extract oil in broiler diet and antioxidant and hypolipidemic in plasma and in the flesh of birds. The experimental design was completely randomized with five treatments and six replicates of 25 birds each. The treatments add the oily extract of anatto (0, 0.714%, 1.428%, 2.142% and 3.571%), to ensure the inclusion of 0; 0.05%; 0.10%; 0.15% and 0.25% bixin, since the oily extract of annatto has 7% of bixin. The performance variables, carcass yield, yield of cuts and abdominal fat were not affected by treatments. There was a linear increase in b * values ​​(yellow intensity) with the inclusion of oily annatto extract. The addition of 0.10% oily extract of annatto in the diet reduced the weight loss by cooking the addition of 0.15% reduced the shear force. There was no treatment effect oxidation variables and lipid profile in flesh and blood of birds. The results of this study allow us to conclude that the oily extract of annatto added to broiler diet did not show hypolipidemic properties in the plasma and in the flesh of birds however, has antioxidant activity in breast and thigh meat